New findings of Decapoda (Crustacea) in the Callovian of the Ryazan region (Central European Russia) - Dadykin, Ivan A.; Shmakov, Alexey S. (Journal of paleontology, 2023)
There are very few articles dedicated to the study of crustacean remains in the marine sediments of the Mesozoic despite the widespread distribution of such remains in Central European Russia. This research is the first general study on decapods of the Ryazan region of Central European Russia and is focused on the Callovian of that area. The Ryazan region is renowned for its large number of outcrops and high concentration of well-preserved marine decapod fossils. Two genera and five species of crustaceans are identified for the first time from Central European Russia. In addition, diagnostic signs of previously noted taxa are factually discussed. The decapod crustaceans of Central European Russia have been the subject of studies since the nineteenth century, and the only species, Eryma quadriverrucatumTrautschold, 1866 (Erymidae), has been found in the Callovian to the Oxfordian of that region. The present paper discusses the new exceptional findings of Solenoceridae, Glypheidae, and Mecochiridae from the upper Callovian sites of the Ryazan Region. The previously reported presence of Archeosolenocera sp. is confirmed in detail; Glypheopsis aff. G. etalloni (Oppel, 1861) and Eumorphia sp. are noticed for the first time for this area. Modern identification of erymids is reported: Eryma aff. E. ventrosum (von Meyer, 1835), E. ornatum (Quenstedt, 1858), and Stenodactylina insignis (Oppel, 1862) are noted in addition to E. quadriverrucatum. These findings address the gaps in the fragmented knowledge about the decapod fauna of Central European Russia and exhibit a differentiation of the local Russian decapod assemblage from those of Western Europe. The decapod community of the Ryazan region is considered to be associated with soft substrates of upper sublittoral zone.